2015
DOI: 10.4028/www.scientific.net/amm.713-715.2859
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Ink Transfer Characteristics for the Anilox

Abstract: Anilox is the most important part in flexography, we simplified the structure of anilox roller into an axisymmetric trapezoidal groove, while established a numerical simulation of the ink transfer process by using the finite element method. We had done research on ink transfer characteristics in the flexographic printing process. The ink transfer ratio decreased when the upper plate contact angle increased, while increased when the dovetail groove contact angle increased; the aspect ratio also have impacts on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…The results showed that the ink transfer rate decreased with an increase in the contact angle of the upper plate and increased with an increase in the contact angle of the trapezoidal groove. The smaller the aspect ratio of the trapezoidal groove and the larger the angular velocity, the higher the ink transfer rate [16]. Therefore, the corresponding anilox roller can be selected to optimize the printing quality.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the ink transfer rate decreased with an increase in the contact angle of the upper plate and increased with an increase in the contact angle of the trapezoidal groove. The smaller the aspect ratio of the trapezoidal groove and the larger the angular velocity, the higher the ink transfer rate [16]. Therefore, the corresponding anilox roller can be selected to optimize the printing quality.…”
Section: Introductionmentioning
confidence: 99%
“…Deganello et al analysed the production of conductive tracks on micro level using different anilox volumes [33]. Cherry investigated the ink release characteristics of anilox rollers [34]. By quantifying the physical volume of ink transferred onto the substrate, as well as the optical density, it was shown that deeper cells provide greater capacity but also prevent ink release.…”
Section: Introductionmentioning
confidence: 99%